ANALYSIS OF RISK OF MR. SUELA BROILER CHICKEN BUSINESS IN TIMPAG VILLAGE KERAMBITAN TABANAN - I G. A., Indraprasta; Sukmawati, M. S.; Ardika, I N. (Jurnal Peternakan Tropika, 2017)
This research conducted in the Timpag Village Kerambitan Tabanan. This location, which were selected purposively sampling consideration that there are fluctuations in a population of cattle a significant in the area because there is transfer of land use become the house. In additionthe last few years start many company offer a partnership system to farmers in this area. This research was conducted from 24 October- 24 November 2016. This research to identify sources risk on broiler farm, analyze the influence of production risk and revenues riskbroiler farm, analyze alternative strategy risk management on broiler farm.The data used in this research was primary and secondary data, this data is quantitative and qualitative.Data analyzed by using the method an analysis of risks, income analyzed by analysis income and r/c ratio, analyze alternative strategy risk of management. The result showed source of risk found is weather, disease, elimination chicken and etc. Price risk consists of price day old chick, feed, medicines, vitamins and output prices / selling price chicken. Suela farm get average value R/C of 1,04 during the period observation 10 production. R/C value >1 obtained Suela Farm in the production period I until the X production period. This indicates that in the production period I until X Suela broiler chicken farm experienced advantage.